Letter (copy) : Lorries in Spain - Tewson, Vincent
028-0058-001 HVT/EK/519. Secretary's. 9th March, 1937. Mr. G. Jeger, Organising Secretary, Spanish Medical Aid Committee, 24, New Oxford Street, London, W.C.1. Dear Mr. Jeger, LORRIES IN SPAIN. In confirmation of our telephone conversation this morning I am returning the documents which you enclosed with your letter of the 8th instant as they are not the cards that are required. As I explained on the telephone, the grey cards which are required are those which were issued, presumably by the French military authorities, in respect of the lorries bought in Paris. I am enclosing a copy of a letter I have received from Mr. Stolz which explains the position. In communicating with the people in Spain, I should be glad if you could ask them to reply as early as possible. Yours sincerely, Assistant Secretary. Booklets. Identification Forms. Copy of letter. 292/946/28/58